Introduction to star-tup creation for the smart ecoefficient built environment - Pacheco-Torgal, F. (2020)
This chapter starts by briefly reviewing worrying evidence concerning Earth?s environment. The importance of entrepreneurship is highlighted as a way not only to mobilize the energy of young people in developed countries for a sustainability based new economy. But also to tackle the despair of young people in poor countries that could end in terrorist actions. Dynamics of start-up creation are briefly reviewed. The stigma on startup failure is also briefly addressed. The importance of start-up creation for the smart eco-efficient built environment is highlighted.  An outline of the book is included.